MEKANISME REGULASI SEL - Suharni, Suharni; Nurul Afifa; Shafa Aqila (Yayasan Nusantara Hasana Berdikari, 2026)
The cell cycle is a fundamental biological process that regulates growth, DNA replication, and cell division in a coordinated manner. Cell cycle regulation plays a crucial role in maintaining tissue homeostasis, genome stability, and preventing uncontrolled cell proliferation. Disruptions in cell cycle regulatory mechanisms are known to contribute to various diseases, particularly cancer, through the loss of checkpoint control and excessive activation of proliferation pathways. Therefore, studying cell cycle regulatory mechanisms is crucial to strengthen biological understanding and its clinical implications in the development of molecularly targeted therapies. This study employed a literature review method with a descriptive-analytical approach. Data were obtained from international scientific articles published in reputable databases and analyzed qualitatively to examine the molecular mechanisms of cell cycle regulation, the role of cyclin-CDK complexes, checkpoint systems, CDK inhibitors, and their association with physiological and pathological conditions. The results indicate that cell cycle regulation is primarily controlled by the activity of cyclin-CDK complexes, which operate in a phase-specific and coordinated manner. Checkpoint systems at the G1/S, G2/M transitions, and spindle assembly function as surveillance mechanisms to ensure accurate DNA replication and chromosome division. Regulatory pathways such as Rb-E2F and p53 play a crucial role in arresting the cell cycle upon DNA damage or cellular stress. Furthermore, it has been discovered that the ubiquitin-proteasome-based protein degradation system also plays a role in regulating the stability of cell cycle regulators, thus refining the classical regulatory model that previously focused solely on cyclin-CDK activation. Cell cycle regulation is a highly controlled, dynamic, and integrated biological process, with cyclin-CDK complexes and checkpoint systems playing a central role in determining the continuation of cell proliferation. A comprehensive understanding of these regulatory mechanisms provides a crucial contribution to the development of therapeutic strategies, particularly in the treatment of cancer and other proliferative disorders, through approaches based on cell cycle pathway control.